Improvement of the total mass and operating time of Knapsack sprayer to Propel Cart Sprayer (PCS) - Nordin, Norbaizura; Ahamad Azahari, Ahmad Syakir; Muslim, Maizatul Anis; Kamaruddin, Muhammad Amar (Penerbit UTHM, 2020)
There are two types of background of the farmers which are the large scale and small scale of agriculture. Usually, the large scale farmers will use the motorize Knapsack Sprayer while the small scale farmers will use manual-operated Knapsack Sprayer. The motorize Knapsack Sprayer that uses by the large scale of agriculture farmers’ area is to save the cost and time [1]. Unfortunately, both types of Knapsack Sprayer have their own ineffectiveness and risk especially the manual Knapsack Sprayer. The farmers that use the manual Knapsack Sprayer will have to carry the heavy load at their back while spraying the pesticide. These are a very burden to the farmers, especially for the old farmers. The weight of the mixture carried can be up to 17 kilograms depends on the density of the mixture whereas the safe weight lifting legalize by OSHA is 22.68 kilograms which the load almost near to its limit for average man and will affect the body locomotion and bones structure is carried in a long term period [2]. The total sprayed area per full tank is 44.09 meters square. The process of spraying the pesticide will slow down because the farmers have to bring the heavy load.